Vocal Emotion of Humanoid Robots: A Study from Brain Mechanism. (24th December 2013) - Wang, Youhui; Hu, Xiaohua; Dai, Weihui; Zhou, Jie; Kuo, Taitzong
Abstract : Driven by rapid ongoing advances in humanoid robot, increasing attention has been shifted into the issue of emotion intelligence of AI robots to facilitate the communication between man-machines and human beings, especially for the vocal emotion in interactive system of future humanoid robots. This paper explored the brain mechanism of vocal emotion by studying previous researches and developed an experiment to observe the brain response by fMRI, to analyze vocal emotion of human beings. Findings in this paper provided a new approach to design and evaluate the vocal emotion of humanoid robots based on brain mechanism of human beings.